Epidemiology and Etiology of Sexually Transmitted Infection among Hotel-Based Sex Workers in Dhaka, Bangladesh - Nessa, Khairun (American Society for Microbiology, 2004)
The prevalence of sexually transmitted infections (STIs) and reproductive tract infections (RTIs) among hotel-based sex workers (HBSWs) in Dhaka, Bangladesh, was studied. A total of 400 HBSWs were enrolled in the study during April to July 2002. Endocervical swabs, high vaginal swabs, and blood samples from 400 HBSWs were examined for Neisseria gonorrhoeae (by culture), Chlamydia trachomatis (by PCR), Trichomonas vaginalis (by microscopy), antibody to Treponema pallidum (by both rapid plasma reagin and Treponema pallidum hemagglutination tests), and antibody to herpes simplex virus type 2 (HSV-2) (by enzyme-linked immunosorbent assay). Sociodemographic information as well as gynecological and obstetric information was collected. Among the HBSWs, 228 women (57%) were symptomatic and 172 (43%) were asymptomatic, 35.8% were positive for N. gonorrhoeae, 43.5% were positive for C. trachomatis, and 4.3% were positive for T. vaginalis. A total of 8.5% had syphilis, 34.5% were positive for HSV-2, and 86.8% were positive for at least one RTI or STI. There was no significant difference between the prevalences of STIs among the symptomatic and asymptomatic HBSWs. These data suggested a high prevalence of STIs, particularly gonorrhea and chlamydia, among HBSWs in Dhaka.